Acceptance and adoption determinants of telemedicine in public healthcare institutions - Kokisa E. Phorah; Lovemore Motsi (Curationis)
Background: One of the challenges facing the usage of telemedicine technology in South Africa, particularly in the North West province (NWP), is lack of user acceptance by health care professionals which prevents piloted project to produce the desired outcomes.